Self-compassion and its relationship to psychological well-being among female students at the University of Hail - Alshammari, Rehab Mujzi (Journal of Educational and Psychological Sciences, 2025)
This study aimed to identify the relationship between self-compassion and psychological well-being among female students at the University of Hail. The study followed the descriptive, correlational approach, and the study sample consisted of (175) female students, who were selected by a simple random method. The study tools were: the self-compassion scale prepared by Neff (2003) and translated by Daoud, &Break. (2017), and the psychological well-being scale prepared by Al-Shehri (2023). The results of the study showed that there is a strong positive correlation with statistical significance between self-compassion and psychological well-being among female students at the University of Hail. There were also no statistically significant differences in the level of self-compassion and the level of psychological well-being between outstanding and non-achieving female students at the University of Hail. In light of the results of the study, a set of recommendations.
Keywords: self-compassion; psychological well-being; female students at the University of Hail